Prevalence and genetic characterization of clinically relevant extended-spectrum β-lactamase-producing Enterobacterales in the Gulf Cooperation Council countries - Hadi, Hamad A.; Al-Hail, Hissa; Aboidris, Leena Elsheikh; Al-Orphaly, Mahmood; Ahmed, Mazen A. Sid; Samuel, Bincy Gladson; Mohamed, Hana Adam; Sultan, Ali A.; Skariah, Sini (Frontiers in Antibiotics, 2023)
Introduction: Amongst gram-negative bacteria, Enterobacterales (EB) such as E. coli and K. pneumoniae are the most clinically relevant pathogens in healthcare settings. Infections secondary to these pathogens are widely common but multidrug resistance (MDR) in EB has become a prominent challenge with increased morbidity, mortality as well as cost of management. The escalating global prevalence of MDR in EB has led to limited treatment options, raising an urgent need for novel antimicrobial therapy(s) as well as necessitated detailed studies exploring underlying resistance mechanisms. In EB, the prime antimicrobial resistance mechanisms against β-lactam antibiotics is mainly via the production of β-lactamases particularly Extended Spectrum β-lactamases (ESBL). Even though the Gulf region is witnessing major challenges of infections secondary to MDR gram negative bacteria, the extent of the problem has not been fully evaluated, thus this review aims to address the prevalence and genetic characterization of ESBL producing EB in the Gulf Corporation Council (GCC) countries. Methods: PubMed search was conducted over the past five years looking for published academic articles discussing the epidemiology of MDR EB in the Gulf Cooperation Council (GCC) countries. Results and Conclusions: In the GCC, there is high prevalence rate of MDR EB particularly ESBLs. Prevalence rates of ESBL-EB among the EB in general clinical samples in the GCC region is 21.6-29.3%, with a slightly higher prevalence rate in ICU patients (17.3-31.3%) and in urinary tract infections (25.2-31.7%). ESBL carriers have also been noted in the general community. ESBL EB from the GCC region show high resistance to ampicillin, aztreonam, 3rd/4th generation cephalosporins, fluoroquinolones, and trimethoprim-sulfamethaxazole. Intermediate resistance rates are observed against nitrofurantoin, piperacillin/tazobactam and gentamicin with rising resistance observed against tigecycline. The isolates demonstrate low level resistance to carbapenems, fosfomycin, colistin and amikacin. EB isolates that are concomitant ESBL-producers as well as carbapenem-resistant (ESBL-CREs) have been increasingly reported, demonstrating alarmingly increased antibiotic resistance patterns compared to ESBL EB. The most prevalent genes for ESBL resistance in the EB isolates in the GCC region are: blaCTX-M (subtype Group1) followed by/co-dominated by blaTEM and blaSHV, while the most common carbapenem resistance genes are blaOXA-48 and blaNDM-1 types.